Effectiveness of a single day induction programme in changing medical students' attitudes towards the speciality of forensic psychiatry. (February 2017) - Archer, Ann; Guliani, Joshana; Johns, Francesca; McCartney, Emily; Smith, E Naomi; Ross, Callum C; Sengupta, Samrat; Das, Mrigendra
Objectives: We aimed to investigate the effectiveness of a day visit in changing attitudes towards a high-security forensic psychiatric hospital, with regard to the current recruitment difficulties in psychiatry. Methods: Broadmoor Hospital, a UK high-security psychiatric hospital, runs day visits for medical students, led by doctors. At the beginning and the end of the day students wrote their responses to the question, 'What do you think of Broadmoor?' Attitudes and themes were identified, and their prevalence was analysed. Results: The responses of 296 students were initially analysed; however, 19 responses had to be excluded because they were illegible or incomplete. Before the visit, 15 responses were rated as positive, 169 neutral and 93 negative. After the visit, 205 responses were positive, 69 neutral and three negative. The themes that changed markedly following the visit were those indicating a change to favourable attitude. Conclusions: A single day visit was shown to be effective in altering the attitudes of medical students towards forensic psychiatry within a high-security psychiatric hospital.